2023
DOI: 10.1186/s42494-023-00137-0
|View full text |Cite|
|
Sign up to set email alerts
|

Biomolecular mechanisms of epileptic seizures and epilepsy: a review

Komang Trisna Sumadewi,
Saktivi Harkitasari,
David Christopher Tjandra

Abstract: Epilepsy is a recurring neurological disease caused by the abnormal electrical activity in the brain. This disease has caused about 50 new cases in 100,000 populations every year with the clinical manifestations of awareness loss, bruising, and mobility abnormalities. Due to the lack understanding of the pathophysiology behind the illness, a wide variety of medications are available to treat epilepsy. Epileptogenesis is the process by which a normally functioning brain undergoes alterations leading to the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Leptin has been identified as a neuroprotective agent 9 . The present study reported serum leptin levels of adolescent (12)(13)(14)(15)(16)(17)(18)(19) and young adults (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) adults who were newly-diagnosed and treatment-naive epileptic patients, and compared the levels with those of healthy individuals. To our knowledge, the current study is the first of its kind.…”
Section: S-31mentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin has been identified as a neuroprotective agent 9 . The present study reported serum leptin levels of adolescent (12)(13)(14)(15)(16)(17)(18)(19) and young adults (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) adults who were newly-diagnosed and treatment-naive epileptic patients, and compared the levels with those of healthy individuals. To our knowledge, the current study is the first of its kind.…”
Section: S-31mentioning
confidence: 99%
“…On the global scale, epilepsy is the 5th most prevalent neurological disorder, following stroke, migraine, dementia and meningitis 4 . Epileptogenesis refers to the exaggerated transformation of a typically functioning brain, resulting in the onset of epilepsy 14 . This process induces molecular modifications in the hippocampus, including changes in neurogenesis and heightened levels of neurotrophic factors and proteins.…”
Section: S-31mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond neurotransmitter signaling, imbalances in other neurotransmitter systems, such as serotonin, dopamine, and acetylcholine, are implicated in epilepsy pathophysiology [ 94 ]. Additionally, alterations in proteins regulating neuronal excitability and synaptic plasticity, including neurotransmitter receptors and ion channels, further influence seizure susceptibility [ 91 , 95 ]. Moreover, neuroinflammation, characterized by the activation of microglia and the release of pro-inflammatory cytokines, can alter neuronal excitability and contribute to seizure progression [ 96 ].…”
Section: Neurological Disorders and Cannabis Studiesmentioning
confidence: 99%
“…Convulsions emerge due to an imbalance between excitatory and inhibitory systems within the central nervous system. Based on distinct electrophysiological and clinical characteristics, seizures have recently been categorized into focal and generalized convulsive, as well as non-convulsive epilepsies [3][4].…”
Section: Introductionmentioning
confidence: 99%